2013
DOI: 10.1016/j.febslet.2013.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the (E)‐4‐hydroxy‐3‐methyl‐but‐2‐enyl‐diphosphate reductase from Plasmodium falciparum

Abstract: a b s t r a c tTerpenoid precursor biosynthesis occurs in human and many pathogenic organisms via the mevalonate and 2-C-methyl-D-erythritol-4-phosphate (MEP) pathways, respectively. We determined the X-ray structure of the Fe/S containing (E)-4-hydroxy-3-methyl-but-2-enyl-diphosphate reductase (LytB) of the pathogenic protozoa Plasmodium falciparum which catalyzes the terminal step of the MEP pathway. The cloverleaf fold and the active site of P. falciparum LytB corresponds to those of the Aquifex aeolicus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…The authors concluded that Fd was most likely to attach to a shallow well formed by the N terminus, helix a1B, and the loops near strands b4A and b4B. Our FNR-Fd-HDR docking simulations indicated that one of the lowest energy ternary complexes had a molecular surface that was very similar to that suggested previously (Rekittke et al, 2013). Interestingly, six residues purportedly involved in the Fd-HDR interaction differed between the major and minor Fd isoforms of peppermint GTs (Glu-54, Lys-55, Thr-57, Lys-69, Glu-73, and Ala-85 in the major isoform corresponded to Val-54, Ser-55, Ser-57, Asn-69, Gln-73, and Ser-85 in the minor isoform, respectively; Fig.…”
Section: Occurrence Of Gt-specific Fd/fnr Isoforms In Monoterpene-accsupporting
confidence: 79%
See 4 more Smart Citations
“…The authors concluded that Fd was most likely to attach to a shallow well formed by the N terminus, helix a1B, and the loops near strands b4A and b4B. Our FNR-Fd-HDR docking simulations indicated that one of the lowest energy ternary complexes had a molecular surface that was very similar to that suggested previously (Rekittke et al, 2013). Interestingly, six residues purportedly involved in the Fd-HDR interaction differed between the major and minor Fd isoforms of peppermint GTs (Glu-54, Lys-55, Thr-57, Lys-69, Glu-73, and Ala-85 in the major isoform corresponded to Val-54, Ser-55, Ser-57, Asn-69, Gln-73, and Ser-85 in the minor isoform, respectively; Fig.…”
Section: Occurrence Of Gt-specific Fd/fnr Isoforms In Monoterpene-accsupporting
confidence: 79%
“…4). The electron transfer reactions of reductive steps of the MEP pathway, catalyzed by 1-hydroxy-2-methyl-2-(E)-butenyl-4-diphosphate synthase (HDS) and 1-hydroxy-2-methyl-2-(E)-butenyl-4-diphosphate reductase (HDR), employ Fd and FNR (Seemann et al, 2006;Rekittke et al, 2013). This cofactor requirement is in accordance with our modeling prediction that Fd recycling is essential for monoterpene biosynthesis (Table I).…”
Section: Fermentation Is Active In Peppermint Gtsmentioning
confidence: 99%
See 3 more Smart Citations